An Efficient Photonic Crystal Fiber-Based Brillouin Erbium Fiber Laser Using a Fiber Bragg Grating for Multi-Wavelength Generation - Shahabuddin, Nurul Shahrizan; Ahmad, Harith; Othman, M.; Md Ali, Sawal Hamid; Yusoff, Zulfadzli; Harun, Sulaiman Wadi (Taylor & Francis, 2011)
An efficient multi-wavelength Brillouin erbium fiber laser is demonstrated using an improved configuration with a broadband fiber Bragg grating and a piece of photonic crystal fiber. The laser generates more than 55 lines of optical comb with a line spacing of approximately 0.09 nm in a 1,565-5 nm region using pump powers of 3 dBm and 150 mW for the Brillouin and 980-nm pumps, respectively. The Brillouin erbium fiber laser with a fiber Bragg grating's reflectivity of 50% obtained a higher number of comb lines compared to that of 99% reflectivity.